Association between gut microbiota and hepatocellular carcinoma from 2011 to 2022: Bibliometric analysis and global trends - Chen, Zhitao; Ding, Chenchen; Gu, Yangjun; He, Yahui; Chen, Bing; Zheng, Shusen; Li, Qiyong (Frontiers in Oncology, 2023)
Background Hepatocellular carcinoma (HCC) is a primary malignant tumor that responsible for approximately 90% of all liver cancer in humans, and is a one of the leading public health problems worldwide. The gut microbiota is a complex microbial ecosystem that affects tumor formation, metastasis and resistance to treatment. Understanding potential mechanisms of gut microbiota pathogenesis is critical for HCC prevention and treatment. methods An English literature search covering 2011–2022 was performed for studies on gut microbiota and HCC in Web of Science Core Collection (WoSCC) database. Bibliometric analysis tools, including VOSviewer, CiteSpace, and R studio were utilized to analysis the global trends and hotspots in research of the connection between gut microbiota and HCC. Results A total of 739 eligible publications, including 383 articles and 356 reviews, were included in the subsequent analysis. Over the past 11 years, the annual number of publications and average citation level have developed rapidly, particularly in the last five years. Meanwhile, we found that the majority of published articles regarding this topic have their origin in the China (n = 257, 34.78%), followed by United States of America (n = 203, 27.47%), and Italy (n = 85, 11.50%). American scholars hold a high productivity, prominence, and the effects of academic environment in the research of this subject. Additionally, University of California, San Diego published the most papers (n = 24) and has the highest average citation value (value = 152.17) in the research of the connection between gut microbiota and HCC. Schnabl B from USA and Ohtani N from Japan were the authors with the highest publications and average citation value, respectively. Bile acid, hepatitis B and dysbiosis were the latest keywords with strong citation bursts in recent years. Conclusion In recent years, the research of gut microbiota in the field of HCC has made rapid progress. The present study demonstrated that bile acid, hepatitis B and dysbiosis were emerging trends and hot spots in the research of the connection between gut microbiota and HCC. We also found that gut microbiota is crucial in the pathogenesis and oncotherapy of HCC through published literature review.